Summary of the Report on Workforce Management Options and Infrastructure Rationalisation of Primary Health Care - Planning Commission (Planning Commission, 2005)
The Ministry of Health and Family Welfare and Planning Commission, Government of India entrusted the study on the “Workforce Management Options & Infrastructure Rationalisation of Primary Health Care System” to the National Council of Applied Economic Research (NCAER) in 2001. The study design was prepared under the guidance of the Steering Group headed by Adviser (Evaluation), Planning Commission (the constitution and the Terms of Reference of the Group are given in Annexure-I). During the course of the study, the Group met six times to guide NCAER study team at different stages to bring out such findings and suggestions that could be acted upon by the planners and policy makers.
Conducted by National Council of Applied Economic Research (NCAER), New Delhi and Programme Evaluation Organisation Planning Commission Government of India New Delhi